Assessment of vibration isolation in «Flexible connector– pipeline–vibration isolators Pendants» mechanical system - Yu. A. Burian; A. V. Zubarev; S. N. Polyakov (Омский научный вестник)
When designing pipeline systems, the question of reducing the vibration load transmitted from vibroactive elements (pumping units, compressors, etc.) through the pipelines to the base almost always arises. In this case, as a rule, when laying pipes, one end is connected to a vibration source through flexible elements (bellows, elastic compensators, pipes). The pipeline is installed on hangers with vibration dampers. The paper considers the issues of calculating the mechanical resistance of flexible connectors, pipelines and vibration isolators of suspensions, as well as analytical dependences and the results of numerical calculation of the forces transmitted to the base and the radiated power depending on the frequency. The graphic materials show the frequency characteristics of the forces on the base and vibration power, depending on the considered mechanical system parameters.